Generation of Phd2-haplodeficient macrophages with proresolution effects for the treatment of limb ischemia - Alves, Patrícia Terra; Moura, Sayone Andrade de; Taylor, Helen; Fidanza, Antonella; Gil, Cristiane Damas; Martin, Leonardo; Nasare, Aléx Martins; Lengert, André van Helvoort; Garcia, Bianca Bonetto Moreno; Guarache, Gabriel Cicolin; Pereira, Gustavo Jose da Silva; Jun Koh, Ivan Hong; et al. (Frontiers in Pharmacology, 2025)
BackgroundPHD2-haplodeficient macrophages (MØs) are promising candidates for the treatment of ischemia-related conditions due to their capacity to modulate the ischemic microenvironment. However, their in vitro generation and therapeutic potential have not yet been established.PurposesThis study aimed to generate Phd2+/− MØs from mouse embryonic stem cells (ESCs) and to assess their functional properties in vitro as well as their therapeutic efficacy in a murine model of limb ischemia.MethodsPhd2+/− MØs were produced by CRISPR–Cas9-mediated disruption of one Phd2 allele in E14IV ESCs, followed by in vitro differentiation. The resulting cells were characterized by flow cytometry, RT–qPCR, and functional assays to evaluate phagocytosis, angiogenic activity, and paracrine effects under normoxic and hypoxic conditions. Therapeutic efficacy was tested in a murine hindlimb ischemia model through intramuscular injection, with recovery monitored by laser Doppler perfusion imaging, muscle mass measurement, and histological analysis of regeneration and neovascularization.ResultsGene-edited E14IV ESCs yielded Phd2+/− MØs (C22-E14IV-MØs) with approximately 50% lower Phd2 expression, minimal ESC marker expression, and predominant CD206 positivity, with ∼50% of cells also expressing MHCII. In addition to generating a functional haplodeficient model, CRISPR/Cas9 editing of a non-coding intronic segment of Egln1 produced a stable ∼50% reduction in Phd2 protein levels. This quantitative decrease is compatible with a cis-acting effect on Egln1 expression, while preserving the integrity of the coding sequence. These macrophages exhibited enhanced phagocytosis, increased secretion of proangiogenic factors, and improved promotion of endothelial tube formation. In vivo, C22-E14IV-MØ treatment significantly enhanced blood perfusion and increased vessel formation in ischemic muscle.ConclusionESC-derived Phd2+/− MØs display robust proresolution and proangiogenic activities, promoting functional recovery in ischemic muscle. These findings support their potential as a novel cell-based therapy for ischemia-related conditions and highlight the opportunity to develop patient-specific Phd2+/− MØs from induced pluripotent stem cells (iPSCs) for future clinical application.